Studies of Entomological Parameters and Perception of Malaria Transmission on the Kwame Nkrumah University of Science and Technology campus, in the Ashanti Region of Ghana - Coleman, Sylvester (2011)
A Thesis submitted for the award of a degree of Master of Science in Clinical Microbiology